Function Over Form: Modeling Groups of Inherited Neurological Conditions in Zebrafish - Kozol, Robert A.; Abrams, Alexander J.; James, David M.; Buglo, Elena; Yan, Qing; Dallman, Julia E. (Frontiers in Molecular Neuroscience, 2016)
Zebrafish are a unique cell to behavior model for studying the basic biology of human inherited neurological conditions. Conserved vertebrate genetics and optical transparency provide in vivo access to the developing nervous system as well as high-throughput approaches for drug screens. Here we review zebrafish modeling for two broad groups of inherited conditions that each share genetic and molecular pathways and overlap phenotypically: cognitive neurodevelopmental disorders such as Autism Spectrum Disorders, Intellectual Disability and Schizophrenia, and neurodegenerative diseases, such as Cerebellar Ataxia, Hereditary Spastic Paraplegia and Charcot-Marie Tooth disease. We also conduct a small meta-analysis of zebrafish orthologues of high confidence neurodevelopmental disorder and neurodegenerative disease genes by looking at duplication rates and relative protein sizes. In the past zebrafish genetic models of these neurodevelopmental disorders and neurodegenerative diseases have provided insight into cellular, circuit and behavioral level mechanisms contributing to these conditions. Moving forward, advances in genetic manipulation, live imaging of neuronal activity and automated high-throughput molecular screening promise to help delineate the mechanistic relationships between different types of neurological conditions and accelerate discovery of therapeutic strategies.